2013
DOI: 10.1161/circep.113.000334
|View full text |Cite
|
Sign up to set email alerts
|

Subepicardial Action Potential Characteristics Are a Function of Depth and Activation Sequence in Isolated Rabbit Hearts

Abstract: V entricular electric propagation is governed by activation sequence, electric properties of the myocardial syncytium, and anatomy of the ventricular wall.1,2 Time course and rate of propagation of the action potential (AP) depends on ionic current flow across sarcolemmal membranes and the electric resistance and capacitance of nearby myocardium. 3 These factors are heterogeneous across the ventricular wall; because of polarized gap junction distribution, intercellular resistance depends on myocardial fiber o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 45 publications
4
36
0
Order By: Relevance
“…Recently this relationship was examined in using AP measurements in all 3 dimensions of the myocardium. The study concluded that dV/dtmax was unaffected by propagation direction deep within the myocardium and that AP rise time was a dictated by a balance between INa and the downstream axial current developed by the myocardium [56].…”
Section: β-Adrenergic Signalling In the Heartmentioning
confidence: 99%
“…Recently this relationship was examined in using AP measurements in all 3 dimensions of the myocardium. The study concluded that dV/dtmax was unaffected by propagation direction deep within the myocardium and that AP rise time was a dictated by a balance between INa and the downstream axial current developed by the myocardium [56].…”
Section: β-Adrenergic Signalling In the Heartmentioning
confidence: 99%
“…This is just enough current to excite longitudinally but not transversely, with a partial activation of the fast sodium channel (Boyle et al, 2012). The electrotonic loading is also lower near the boundary due to the boundary condition, so a lower transmembrane current density is required to excite tissue down the concentration gradient (Kelly et al, 2013; Bishop et al, 2014). In addition, the high extracellular conductivity adjacent to the boundary (in the bath space) significantly increases the conduction velocity of the wave close to the surface (Henriquez et al, 1996, 2007; Bishop and Plank, 2011; Bishop et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it will provide an essential tool to facilitate a closer, and essential, validation of the predictions made from computational simulation results using these latest highly-detailed MR-based models with optical mapping recordings which, until now, has not been possible. Secondly, it will provide important insight into the underlying mechanisms of fluorescent signal distortion and the role of fine-scale structures, which may be of significant importance in facilitating a better interpretation of optical mapping signals from high-resolution imaging systems (Bub et al, 2010; Kelly et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Many optical mapping studies in recent years have used careful measurements of both upstroke durations and morphologies from the epicardial surface to infer detailed information regarding localized subsurface wavefront direction (Hyatt et al, 2003, 2005) and relative electrotonic loading (Kelly et al, 2013). Although, in this study we highlighted the significantly different effects on the upstroke due to the interaction of the wavefront with large sub-epicardial cavities for different overall global wavefront propagation directions (toward and parallel to the recording surface), the interaction with localized subsurface wavefront orientations with cavities may also represent an important consideration.…”
Section: Discussionmentioning
confidence: 99%